IKZF1 deletion is an independent predictor of outcome in pediatric acute lymphoblastic leukemia treated according to the ALL-BFM 2000 protocol - Dörge, Petra; Meissner, Barbara; Zimmermann, Martin; Möricke, Anja; Schrauder, André; Bouquin, Jean-Pierre; Schewe, Denis; Harbott, Jochen; Teigler-Schlegel, Andrea; Ratei, Richard; Ludwig, Wolf-Dieter; Köhler, Rolf; et al. (Haematologica, the hematology journal, 2013)
IKZF1 gene deletions have been associated with a poor outcome in pediatric precursor B-cell acute lymphoblastic leukemia. To assess the prognostic relevance of IKZF1 deletions for patients treated on Berlin-Frankfurt-Münster Study Group trial ALL-BFM 2000, we screened 694 diagnostic acute lymphoblastic leukemia samples by Multiplex Ligation-dependent Probe Amplification. Patients whose leukemic cells bore IKZF1 deletions had a lower 5-year event-free survival (0.69±0.05 vs. 0.85±0.01; P